Headache-specific hyperexcitation sensitises and habituates on different time scales: An event related potential study of pattern-glare - Cihan Dogan; Claire E. Miller; Tom Jefferis; Margarita Saranti; Austyn J. Tempesta; Andrew J. Schofield; Ramaswamy Palaniappan; Howard Bowman (NeuroImage: Reports, 2025)
Cortical hyperexcitability is a key pathophysiological feature in several neurological disorders, including migraine, epilepsy, tinnitus, and Alzheimer's disease. We examined the temporal characteristics of Event Related Potentials (ERPs) in a healthy population using the Pattern Glare Test, a diagnostic tool used to assess patients with sensitivity to cortical hyperexcitability. In pre-experiment questionnaires, participants reported their susceptibility to a range of symptoms. A factor analysis over these responses identified three variables, with the one we investigate in this paper loading strongly on headache symptoms, e.g. headache frequency. We investigated two timeframes: habituation over the course of the entire experiment and sensitization over the course of a sequence of stimulus presentations. We found evidence of hyperexcitability at electrodes over visual cortex, for the aggravating stimulus (grating of ∼3 cycles/deg). Participants higher on the headache factor exhibited a higher degree of habituation and sensitization, with evidence that the level of sensitization habituated through the course of the experiment. These findings suggest that the same experimental paradigm and analysis should be performed on a clinically diagnosed population.